РЕЗУЛЬТАТЫ ОБРАБОТКИ ОБЗОРА НА 102.5 МГЦ: КАТАЛОГ РАДИОИСТОЧНИКОВ ДЛЯ СКЛОНЕНИЙ +14,1°...+82°, РЕЗУЛЬТАТЫ ЕГО СРАВНЕНИЯ С ДРУГИМИ КАТАЛОГАМИ - Дагкесаманский, Р. Д.; Самодуров, В. А.; Гадельшин, Д. Р.; Семенюк, П. Н.; Кравченко, Е. В. (Одеські астрономічні публікації, 2011)
The results of data processing of the North Sky Survey at 102.5 MHz observations made with BSA FIAN radiotelescope in 1991-93 are given. As a result, the whole sky was covered in declinations –16°<δ<+82°. The part of radio sources catalog with fluxes more than 3 Jy and declinations in +14,1°...+33,5° and +60°...+82° ranges are published and reported early. In this work reported results for 14,1°...+82° sky zone (more than 7 thousands radio sources). The observational techniques and the data reduction are described, and the catalogue reliability and completeness are analyzed.